Treatment of Hepatocellular Carcinoma by Intratumoral Injection of 125I-AA98 mAb and Its Efficacy Assessments by Molecular Imaging - Zhou, Jun; Hu, Pengcheng; Si, Zhan; Tan, Hui; Qiu, Lin; Zhang, He; Fu, Zhequan; Mao, Wujian; Cheng, Dengfeng; Shi, Hongcheng (Frontiers in Bioengineering and Biotechnology, 2019)
Objective: To investigate the therapeutic efficacy of intratumoral injection of 125I-AA98 mAb for hepatocellular carcinoma (HCC) and its therapy efficacy assessment by 99mTc-HYNIC-duramycin and 99mTc-HYNIC-3PRGD2 SPECT/CT imaging. Methods: HCC xenograft tumor mice models were injected intratumorally with a single dose of normal saline, 10 μCi 125I-AA98 mAb, free 125I, AA98 mAb, 80 μCi 125I-AA98 mAb and 200 μCi 125I-AA98 mAb. 99mTc-HYNIC-duramycin and 99mTc-HYNIC-3PRGD2 micro-SPECT/CT imaging were performed on day 3 and day 7, respectively. The T/M ratio for each imaging was compared with the corresponding immunohistochemical staining at each time point. The relative tumor inhibition rates were documented. Results: In terms of apoptosis, the 200 μCi group demonstrated the highest apoptotic index (11.8 ± 3.8%), and its T/M ratio on day 3 was higher than that of the normal saline group, 10 μCi group and free 125I group on day 3, respectively (all P < 0.05). The T/M ratio in the 80 μCi group on day 3 was higher than that in the 10 μCi and normal saline groups on day 3 (both P < 0.05). On day 3, there was a markedly positive correlation between T/M ratio and apoptotic index by TUNEL staining (r = 0.6981; P < 0.05). The 200 μCi group showed the lowest T/M ratio on 99mTc-HYNIC-3PRGD2 imaging (1.0 ± 0.5) on day 7 (all P < 0.05). The T/M ratio of 99mTc-HYNIC-3PRGD2 imaging on day 7 in the 80 μCi group and AA98 mAb group were both higher than that in the 10 μCi group and normal saline group (all P < 0.05). The T/M ratio on day 7 was not correlated with integrin ανβ3 staining (P > 0.05). The relative inhibitory rates of tumor on day 14 in the AA98 mAb, 10 μCi, 80 μCi, free 125I and 200 μCi groups were 26.3%, 55.3%, 60.5%, 66.3% and 69.5%, respectively. Conclusion: The 125I-AA98 mAb group to treat CD146 high expression Hep G2 HCC mouse mode would better play the role of 125I short-range irradiation to cause tumor apoptosis and AA98 mAb as an anti-angiogenetic inhibitor, and 125I-AA98 mAb has a potential to treat HCC.